Advancing crop disease early warning in South Asia by complementing expert surveys with internet media scraping - Smith, Jacob W.; Faisal, Asif Al; Hodson, David P.; Baidya, Suraj; Bhatta, Madan; Dhruba Bahadur Thapa; Basnet, Roshan; Thurston, William; Krupnik, Timothy J.; Gilligan, Christopher A. (Wiley, 2024)
Wheat contributes one-fifth of the global food supply with an estimated 29% of global production in low and lower-middle income countries. As production expands across southern Asia, yields are often negatively impacted by outbreaks of fungal rust diseases. A wheat rust early warning and advisory system comprising surveillance, near real-time disease risk forecasts and advisory dissemination has been established in two target countries in South Asia, including Nepal and Bangladesh. However, as wheat rust spores can be aerially transmitted over long distances, near real-time estimates of disease incidence are required from sources of infection in neighbouring regions. To address this challenge, we developed and tested a novel algorithm to generate proxy observations of infection sources using online media reports in two neighbouring countries, India and Pakistan. Media sampling could provide an effective alternative where data from ground surveys are not readily available in near real-time. Our results show that west Nepal was exposed to a substantial inoculum pressure from aerially dispersed stripe rust spores originating from India and Pakistan. There were no outbreaks of stripe rust disease in Bangladesh with only very low levels of cross-border dispersion and generally unfavourable environmental conditions for infection. We further describe how proxy observations informed farmer decision-making in near real-time in Nepal and filled a knowledge gap in identifying early sources of infection for a major outbreak of stripe rust during 2020 in Nepal. Our results highlight the importance of international cooperation in mitigating transboundary plant pathogens.